Determinants of Consumptive Behavior of Generation Z: The Moderating Role of Financial Literacy - Mukmin Mukmin; Jufrizen Jufrizen; Nadia Ika Purnama; Ade Gunawan; Satria Tirtayasa (Postgraduate Program Merdeka University, 2022)
The purpose of this study was to determine the effect of Lifestyle, Self-Concept and Peer Groups on Consumptive behavior, and to examine the role of Financial Literacy in moderating the influence of Lifestyle, Self-Concept and Peer Groups on Consumptive behavior. This study uses a quantitative approach. To determine the size of the sample used Maximum Likelihood estimation in the Structural Equation Model (SEM) of 100-200 samples, then researchers will take a sample of 100-200 respondents to fulfill one of the requirements for a data analysis approach using SEM. As a result, as many as 167 students were used as research samples. The results of the study show that lifestyle, self-concept and peer groups have a positive and significant effect on consumptive behavior. Financial Literacy does not play a role in moderating the effect of Lifestyle and self-concept on Consumptive behavior. Financial Literacy plays a role in moderating the influence of Peer Groups on Consumptive behavior.DOI: https://doi.org/10.26905/afr.v5i3.9514